2007
DOI: 10.1111/j.1432-2277.2007.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular events after liver transplantation: a long-term follow-up study

Abstract: Summary Long‐term follow‐up studies on the impact of vascular events (VE) and risk factors of liver transplant recipients are scarce. In this study, 311 recipients of a first isolated liver transplant who survived at least 1 year were followed up from 1979 to 2002. The median follow‐up duration was 6.2 (range1–22.7) years. Overall median survival was 18.7 [95% confidence interval (CI): 15.5–20.1] years and this was significantly lower compared with age‐ and sex‐matched controls. Eleven (21%) of the patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
2
31
0
1
Order By: Relevance
“…Other complications associated with smoking are increased risks of infection,19 hepatic artery thrombosis and stenosis,20 and biliary complications 21. Furthermore, smoking is also a risk factor for cardiovascular disease,19, 22 and this is one of the most frequent causes of late mortality after liver transplantation 6. With this scenario, if the findings of this article are confirmed in larger series, all liver transplant candidates should be counseled against smoking.…”
Section: Discussionmentioning
confidence: 85%
“…Other complications associated with smoking are increased risks of infection,19 hepatic artery thrombosis and stenosis,20 and biliary complications 21. Furthermore, smoking is also a risk factor for cardiovascular disease,19, 22 and this is one of the most frequent causes of late mortality after liver transplantation 6. With this scenario, if the findings of this article are confirmed in larger series, all liver transplant candidates should be counseled against smoking.…”
Section: Discussionmentioning
confidence: 85%
“…Five studies had patient cohorts with limited representativeness compared to the overall patient population of interest and 1 study only provided limited data regarding the patient cohort. 14,19,24,3335 Among the cardiac imaging studies, 2 studies were assessed as having limited representativeness given the inclusion and exclusion criteria. 20,30 …”
Section: Resultsmentioning
confidence: 99%
“…Their work indicates an increased risk of overall, cardiovascular‐specific, and sepsis‐specific mortality with smoking [40]. Other recent studies have demonstrated that smoking is associated with inferior long‐term cardiovascular and oncologic outcomes following liver transplantation [2,4,5,41–44]. With regard to perioperative outcomes, smoking was also associated with increased resource utilization and hospital charges following liver transplantation in a series of 65 liver transplants over a 2‐year period at the University of Kentucky [45].…”
Section: Discussionmentioning
confidence: 99%